Justice Constitutionality of Specialized Court in Coping with the Dispute on Direct Local Leader Election Result - Marwi, Ebin (Faculty of Law, Mulawarman University, 2018)
In accordance with the petition of Constitutional Court Number 97/PUU-XI/2013, Constitutional Court is no longer authorized to resolves disputes on direct Local Leader Election result, because provisions of Article 236C of Law Number 12 Year 2018 Republic of Indonesia against the constitution of 1945 Article 157 paragraph (1) Law Number 8 Year 2018 determines that the dispute settlement on direct Local Leader Election results become the authority of specialized judiciary. But before a specialized judiciary is formed, then the Constitutional Court is authorized to resolve disputes on direct Local Leader Election results. The authority of the Constitutional Court is the constituional authority to fulfill temporary vacuum of norm (rechtvakum). Therefore Legislators should immediately establish a specialized judiciary which has the authority to resolve the disputes on direct Local Leader Election result.